2017
DOI: 10.3390/w9060397
|View full text |Cite
|
Sign up to set email alerts
|

Constructed Wetlands for Water Treatment: New Developments

Abstract: Constructed wetlands (CWs) are currently regarded as established eco-technologies to treat water pollution. Although considered near-natural systems, they are totally engineered solutions for which research has been actively developed over the past decades. This paper provides a brief meta-analysis on the latest scientific publications in the field and an overview of the special issue focused on the new developments in the use of CWs for water treatment. The selected papers cover a wide range of relevant devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Before analysis, all samples were filtrated through Watman 42 filters (Merck KGaA, Darmstadt, Germany). The samples taken and analysed for nutrient concentrations at inlet (C in , mg•L −1 ) and outlet (C out , mg•L −1 ) were multiplied by the related measured volume of water that flowed into (V in , m 3 ) or out (V out , m 3 ) of the system, respectively. Afterwards, all the inflow and outflow loads during one hydrological year were summed to calculate the mass of nutrients (kg•year −1 ) entering and exiting the wetland yearly.…”
Section: Water Balance and Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Before analysis, all samples were filtrated through Watman 42 filters (Merck KGaA, Darmstadt, Germany). The samples taken and analysed for nutrient concentrations at inlet (C in , mg•L −1 ) and outlet (C out , mg•L −1 ) were multiplied by the related measured volume of water that flowed into (V in , m 3 ) or out (V out , m 3 ) of the system, respectively. Afterwards, all the inflow and outflow loads during one hydrological year were summed to calculate the mass of nutrients (kg•year −1 ) entering and exiting the wetland yearly.…”
Section: Water Balance and Qualitymentioning
confidence: 99%
“…Compared to conventional wastewater treatment plants, CWs are less costly, easier to operate, and require less maintenance [2]. In addition to their general ability to improve wastewater quality, CWs are multifunctional systems that can offer different ecosystem services [3], including supporting habitat and biodiversity functions, together with recreational and socioeconomic services, including flood and drought control, water retention, and erosion prevention [4][5][6]. These systems can also be used as a part of water reuse schemes [7,8] and can have positive effects on carbon balance [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The P-k-C* model was applied [12,17,18]. The issue of modeling the functioning of constructed wetlands is one of the most important challenges in that field [19,20]. The current models of pollutant removal concern the municipal and industrial wastewater treatment, whereas there is no such model for reject water treatment, so the necessity for such research goals was confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…Constructed wetlands (CWs) are particularly well suited for wastewater treatment in small communities, i.e., those with a <2.000 p.e. (person equivalent) because of their low cost, easy maintenance, high treatment efficiency, and visual appeal [1]. Similarly, CWs are environmentally friendly and a real alternative for the treatment of different types of wastewaters [2].…”
Section: Introductionmentioning
confidence: 99%